2017
DOI: 10.15406/jabb.2017.03.00084
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Activity of the Autonomic Nervous Systems of Healthy and Hypertensive Patients in Russia

Abstract: Objective: Evaluation of the gender difference in the activity of the autonomic nervous systems of healthy and hypertensive patients in Russia. Materials and Methods:The methods of heart rate variability (HRV) and gas discharge visualization (GDV or electrophotonic Imaging/EPI) were used to assess subjects. Analysis of data from 138 patients with different stages of arterial hypertension, aged 20 to 70 years, and 37 healthy ones was carried out. Results:The differences in the activity of the autonomic nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Additionally, contrary to the fact that females have higher HR than males, both in humans and mice (Prabhavathi et al, 2014 ; Yang et al, 2007 ), our study showed the opposite phenomena across control and pancreatic liver groups. This is a curious discrepancy since several studies have reported in humans and conscious rats that healthy females have higher parasympathetic activity than males, which agrees with our findings (Korotkov, 2017 ; Yaghouby et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, contrary to the fact that females have higher HR than males, both in humans and mice (Prabhavathi et al, 2014 ; Yang et al, 2007 ), our study showed the opposite phenomena across control and pancreatic liver groups. This is a curious discrepancy since several studies have reported in humans and conscious rats that healthy females have higher parasympathetic activity than males, which agrees with our findings (Korotkov, 2017 ; Yaghouby et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…MxDMn is the difference between A REASONABLE OFFICER minimum and maximum R-R intervals represents the amount of variation. Under psychological or physical stress the distribution of the histogram constricts, while simultaneously increasing in height(Korotkov, 2017). Therefore, high Stress Index values indicate reduced variability and increased SNS activation(Kubios Oy, 2021).…”
mentioning
confidence: 99%